IMPLEMENTASI METODE HEAT DALAM MENANGANI KELUHAN TAMU DI HOTEL THE PREMIERE PADANG - Ditha Triana Hendari; Dwi Pratiwi Wulandari (Ensiklopedia of Journal, 2023)
This research began with the results of observations, pre-interview research and observations of the author when conducting industrial field practice at The Premiere Padang Hotel, that it was found that there were guests who felt that the staff did not listen to the complaints submitted. Then the guest feels a lack of empathy from the staff to the guest, besides that there is no apology from the staff when there is a guest complaint, and there is no continuation of a complaint that occurs. This study aims to analyze how the implementation of the HEAT method in handling guest complaints at The Premiere Padang Hotel, which is seen from four indicators, namely hear them out, emphatize, apologize, take action and follow up. The method in this study is descriptive with qualitative data. Data collection techniques through interviews and observations to front desk agent staff, one front desk agent supervisor, and three marketing staff, using purposive sampling techniques. The data analysis techniques used are data reduction, data presentation, and drawing conclusions. The results showed that most of the staff at The Premiere Hotel Padang have used the HEAT method in handling guest complaints, but with continued complaints from guests regarding HEAT implementation indicators that were not implemented, the management of The Premiere Hotel Padang should pay more attention to the way the staff handles guest complaints.